2015
DOI: 10.1242/dev.110940
|View full text |Cite
|
Sign up to set email alerts
|

Precise spatial restriction of BMP signaling is essential for articular cartilage differentiation

Abstract: The articular cartilage, which lines the joints of the limb skeleton, is distinct from the adjoining transient cartilage, and yet, it differentiates as a unique population within a contiguous cartilage element. Current literature suggests that articular cartilage and transient cartilage originate from different cell populations. Using a combination of lineage tracing and pulse-chase of actively proliferating chondrocytes, we here demonstrate that, similar to transient cartilage, embryonic articular cartilage c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
117
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(124 citation statements)
references
References 41 publications
7
117
0
Order By: Relevance
“…Moreover, decreased TGFβR2 signaling in the joint region has been shown to impair chondrocyte hypertrophy at embryonic stages via increased expression of the cytokine MCP5 (Longobardi et al, 2012), but we were not able to detect MCP5 mRNA or protein in our model at P3. On the other hand, RNA and protein levels of the WNT target Lef1 were upregulated in the RZ of the left P1-Pit::DTR GP compared to right (Figure 3C; see also Figure 4—figure supplement 2, n = 5 at P3, 4 at P4, 3 at P5), which might impair PTHLH signaling and chondrocyte differentiation, as described (Ray et al, 2015; Guo et al, 2009). In summary, our results show that damage in the tissues adjacent to the early postnatal GPs results in alterations in multiple GP signaling pathways known to regulate bone growth.
10.7554/eLife.27210.007Figure 3.Multiple signaling pathways related to chondrocyte proliferation and maturation are altered in distinct regions of the left P1-Pit::DTR growth plate.( A–A’ ) In situ hybridization for Ihh and the HH target Gli1 , in the left and right proximal tibia of Pit::DTR mice, 2dpi.
…”
Section: Resultsmentioning
confidence: 63%
“…Moreover, decreased TGFβR2 signaling in the joint region has been shown to impair chondrocyte hypertrophy at embryonic stages via increased expression of the cytokine MCP5 (Longobardi et al, 2012), but we were not able to detect MCP5 mRNA or protein in our model at P3. On the other hand, RNA and protein levels of the WNT target Lef1 were upregulated in the RZ of the left P1-Pit::DTR GP compared to right (Figure 3C; see also Figure 4—figure supplement 2, n = 5 at P3, 4 at P4, 3 at P5), which might impair PTHLH signaling and chondrocyte differentiation, as described (Ray et al, 2015; Guo et al, 2009). In summary, our results show that damage in the tissues adjacent to the early postnatal GPs results in alterations in multiple GP signaling pathways known to regulate bone growth.
10.7554/eLife.27210.007Figure 3.Multiple signaling pathways related to chondrocyte proliferation and maturation are altered in distinct regions of the left P1-Pit::DTR growth plate.( A–A’ ) In situ hybridization for Ihh and the HH target Gli1 , in the left and right proximal tibia of Pit::DTR mice, 2dpi.
…”
Section: Resultsmentioning
confidence: 63%
“…Recent evidence indicates that a continuous influx of GDF5 (growth differentiation factor 5) positive cells contributes to joint development (Ray et al ., 2015; Shwartz et al ., 2016). With the upregulation of unique molecules such as Wnt9A (Wingless-Type MMTV Integration Site Family, Member 9A), GDF5, Erg (ets related gene), Gli3 (GLI Family Zinc Finger 3), CD44 (cluster differentiation 44), and type IIA/I collagen (Iwamoto et al , 2007; Koyama et al , 2008; Pacifici et al , 2006), cavitation appears within the interzone (Archer et al , 2003).…”
Section: Vascular Neural and Basic Anatomymentioning
confidence: 99%
“…That this Bmp activity originates in the interdigit has been shown genetically in the mouse (Huang et al, 2016), where it is modulated through Hoxd-Gli3 antaganism. Moreover, GDF5, a divergent member of the Bmp superfamily, is a very early marker of the non-chondrogenic future joint cells (Ray et al 2015), and has been shown to induce chondrogenesis both in vitro and in vivo (Francis-West et al, 1999; Storm and Kingsley, 1949). Wnt activity is also present in the non-chondrogenic interdigit domains.…”
Section: Integrating Joint Formation Into the Picturementioning
confidence: 99%